THE PEDAGOGICAL CONTENT KNOWLEDGE DIMENSIONS OF MATHEMATICS TEACHER IN MATHEMATICS MODELING LEARNING - Elika Kurniadi; Vina Amalia Suganda; Bunda Harini (FKIP Universitas Muhammadiyah Tangerang, 2022)
This study aims to explain the dimensions of pedagogical content knowledge of mathematics teachers in learning mathematical modeling. Four dimensions of teacher pedagogical content knowledge for mathematical modeling: (1) Dimension of mathematical modeling theory, (2) Dimension of cognitive, (3) Dimension of learning, and (4) dimension of evaluation. The data collection is observation and interview. Based on the basic assumptions about the impact of teaching on learning, teacher competence will result in quality teaching and quality student learning. Therefore, all of dimensions should be included as mandatory components in teacher education and professional development.